REAL-TIME SIMULATIVE MODELING FOR GEAR CHANGE CONTROL STRATEGY RESEARCH - A. A. Filimonov; V. A. Kusyak (Наука и техника)
The paper deals with an efficiency estimation of automated mechanical transmission at off-line simulation stage. A simulation model of a vehicle with an automated power unit for gear change control strategy research has been developed in the paper. The paper contains a complex mathematical description of the analysis scheme. It allows adequately to react to structure reorganization and parameter change of the dynamic system at an application of external disturbances from the road and a driver. A peculiar feature of the developed software that is an opportunity of real-time modeling. This decision enables to estimate automated mechanical transmission operation at a wide spectrum of the driver’s actions. The experiment on a driving simulation of a heavy truck with 40000 kg GCW on a road climb has been carried out. The estimated values of driving on a route have been compared  during gear changes in automatic and command modes by drivers of various qualification. The paper contains conclusions about efficiency of the analyzed gear change control strategy. A strategy for improvement of automated mechanical transmission controlling algorithms has been proposed in the paper.